74.3k views
5 votes
A statement Sn about the positive integers is given. Write statements Sk and Sk+1, simplifying Sk+1 completely.

Sn: 1 + 4 + 7 + . . . + (3n - 2) = n(3n - 1)/2

1 Answer

4 votes

If we have


\displaystyle S_n: \sum_(i=1)^n (3i-2)=(n(3n-1))/(2)

in order to write
S_k and
S_(k+1), we simply have to substitute "n" with "k" and "k+1", respectively.

So, we have


\displaystyle S_k: \sum_(i=1)^k (3i-2)=(k(3k-1))/(2)


\displaystyle S_(k+1): \sum_(i=1)^(k+1) (3i-2)=((k+1)(3(k+1)-1))/(2)=((k+1)(3k+3-1))/(2)=((k+1)(3k+2))/(2)=(3k^2+5k+2)/(2)

User Flying Dumpling
by
6.4k points